Lucy Benton: capstone - Benton, Lucy, artist (Colorado State University. Libraries, 2024)
The artist's statement: My practice reflects ideas connected to memory, growth, and ecology, focused on the exploration of the interconnectedness between myself, others, and the natural world. I use my artwork to create a deeper understanding of the intricate world around me, as well as the relationships that shaped my identity. Growing up, I spent countless hours exploring the woods on my grandmother's property in Wisconsin, which led to a keen appreciation of nature. Drawing inspiration from my childhood, my practice is deeply rooted in the organic design of the natural world and how that links with my memories and my perception of self. My work often features the human figure, particularly the female form, serving as a reflection of my own involvement with and connection to the natural world surrounding me. Additionally, imagery depicting the human form serves as a connection to the nurturing energy of influential figures in my life—specifically my mother, aunt, and grandmother. These women have played roles in shaping my perspective and creativity. Using oil paint as my main medium, I incorporate vibrant colors and dynamic textures to evoke the living energy within the world around me. Through these paintings, I explore a combination of both abstract and representational imagery to reflect and explore my place within the world. Heavily inspired by artists like Lois Dodd, Ellen Seibers, Cecily Brown, and Mark Bradford, my artistic style involves a wide variety of mark-making, creating movement and energy within my brushwork. Compositionally, I approach my paintings as an exploration of space, color, and texture as I build my paintings up through many layers. My canvases are often evolving as I add and subtract through imagery and paint.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting